Neoliberal subversion of agrarian reform (IBON Institute for International Development, 2014)
The book was launched by the People’s Coalition on Food Sovereignty (PCFS) together with IBON International and IBON Institute for International Development (I3D) in cooperation with the Pesticide Action Network – Asia Pacific (PAN-AP) and GRAIN-Asia.